Preparation, characterization and application of low-cost pyrophyllite-alumina composite ceramic membranes for treating low-strength domestic wastewater - Jeong, Yeongmi; Lee, Sanghyup; Hong, Seungkwan; Park, Chanhyuk (ELSEVIER SCIENCE BV, 2017)
To advance cost-effective strategies for developing flat-sheet ceramic microfiltration membranes, the feasibility of using waste mineral-based materials as a ceramic membrane in engineered membrane bioreactor systems (MBRs) for treating low-strength domestic wastewater was evaluated. The ceramic membrane support layers that had effectively been fabricated with pyrophyllite and alumina were sintered at 1350 degrees C, and subsequently coated with alumina powder suspension to achieve a narrow pore size distribution. Membrane surface properties were characterized to understand the membrane fouling phenomenon in ceramic MBRs (CMBRs). Consistently high organic removal efficiency could be achieved under all investigated hydraulic retention times (HRTs) in the CMBRs. The physico-chemical sludge properties were measured to evaluate design parameters affecting membrane fouling for the CMBR. We further evaluated the performance of pyrophyllite-alumina composite ceramic membranes in a pilot-scale CMBR plant, with 1 m(3)/d capacity that was constructed at an actual water resource recovery facility (WRRF), to improve nitrogen removal and produce high quality effluent through a combined process of modified Ludzack-Ettinger (MLE) and CMBR (MLE/CMBR). The MLE/CMBR was operated successfully up to 20 LMH, with the final effluent chemical oxygen demand (COD) being maintained below 16.3 mg/L.
Keywords: BIOLOGICAL NUTRIENT REMOVAL; SOLIDS RETENTION TIMES; BIOMASS CHARACTERISTICS; PORE CHARACTERISTICS; ACTIVATED SLUDGES; SUSPENDED-SOLIDS; SUPPORT LAYER; BIOREACTOR; SYSTEM; MICROFILTRATION